Infections in lower-risk myelodysplastic syndromes - prevalence and risk factors: a report from the European MDS Registry - Bente Houtman; Adele Taylor; Corine van Marrewijk; Alexandra Smith; Pierre Fenaux; Catherine Cargo; Argiris Symeonidis; Moshe Mittelman; Reinhard Stauder; Jaroslav Čermák; Guillermo Sanz; Eva Hellström-Lindberg; et al. (Haematologica)
Infections are an important cause of morbidity and mortality in patients with lower-risk myelodysplastic syndromes (LR-MDS). Studies regarding risk factors for infections are, however, limited in this population. This study aimed to investigate the prevalence and risk factors for infections and infection-related death in patients with LR-MDS. This study included 2552 patients from the European MDS (EUMDS) Registry, which prospectively collects observational data on newly diagnosed MDS patients from 17 countries. Prevalence of infections and infection-related death was determined. Risk factors for infections and infection-related death, occurring within one year from diagnosis were analyzed in separate multivariable logistic regression models. A third model that only included LR-MDS patients who experienced an infectious episode within the first year from diagnosis was used to analyze risk factors associated with infection-related death in patients with an infectious episode. The prevalence of infections was 7.6%, and 24.6% of all deaths were due to infections. In multivariable analysis, an independent association with increased risk for infections was found for haemoglobin level <8g/dL, platelet count <50x109/L, absolute neutrophil count <0.8x109/L, cytogenetics intermediate/poor/very poor, and having received red blood cell transfusions at baseline. An independent association with increased risk of infection-related death was found for older age at diagnosis, haemoglobin level <8g/dL, and platelet count <50x109/L. Patients with an increased risk of infections could benefit from close monitoring, especially in the first months after diagnosis. Future research should focus on the causality and severity of infections and risk factors over time, to provide more guidance for monitoring.